Answer:
The perimeter or circumference of a half mirror = 37.68 cm
Step-by-step explanation:
- The diameter of circular measure = 24 cm
We know that the perimeter of a circular shape is called the 'circumference', with the formula
- Circumference of a circle = C = 2πr
When the mirror is cut into half, the diameter gets half as well.
- Thus, the diameter of a half mirror = 24/2 = 12 cm
We know that radius = r = diameter / 2 = 12/2 = 6 cm
Thus, the perimeter of half of the mirror = C = 2πr
= 2(3.14)6
= 37.68 cm
Therefore, the perimeter or circumference of a half mirror = 37.68 cm
(a) We want to find a scalar function
such that
. This means
![\dfrac{\partial f}{\partial x} = 2xy + 24](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%20%3D%202xy%20%2B%2024)
![\dfrac{\partial f}{\partial y} = x^2 + 16](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%20%3D%20x%5E2%20%2B%2016)
Looking at the first equation, integrating both sides with respect to
gives
![f(x,y) = x^2y + 24x + g(y)](https://tex.z-dn.net/?f=f%28x%2Cy%29%20%3D%20x%5E2y%20%2B%2024x%20%2B%20g%28y%29)
Differentiating both sides of this with respect to
gives
![\dfrac{\partial f}{\partial y} = x^2 + 16 = x^2 + \dfrac{dg}{dy} \implies \dfrac{dg}{dy} = 16 \implies g(y) = 16y + C](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%20%3D%20x%5E2%20%2B%2016%20%3D%20x%5E2%20%2B%20%5Cdfrac%7Bdg%7D%7Bdy%7D%20%5Cimplies%20%5Cdfrac%7Bdg%7D%7Bdy%7D%20%3D%2016%20%5Cimplies%20g%28y%29%20%3D%2016y%20%2B%20C)
Then the potential function is
![f(x,y) = \boxed{x^2y + 24x + 16y + C}](https://tex.z-dn.net/?f=f%28x%2Cy%29%20%3D%20%5Cboxed%7Bx%5E2y%20%2B%2024x%20%2B%2016y%20%2B%20C%7D)
(b) By the FTCoLI, we have
![\displaystyle \int_{(1,1)}^{(-1,2)} \mathbf F \cdot d\mathbf r = f(-1,2) - f(1,1) = 10-41 = \boxed{-31}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint_%7B%281%2C1%29%7D%5E%7B%28-1%2C2%29%7D%20%5Cmathbf%20F%20%5Ccdot%20d%5Cmathbf%20r%20%3D%20f%28-1%2C2%29%20-%20f%281%2C1%29%20%3D%2010-41%20%3D%20%5Cboxed%7B-31%7D)
![\displaystyle \int_{(-1,2)}^{(0,4)} \mathbf F \cdot d\mathbf r = f(0,4) - f(-1,2) = 64 - 41 = \boxed{23}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint_%7B%28-1%2C2%29%7D%5E%7B%280%2C4%29%7D%20%5Cmathbf%20F%20%5Ccdot%20d%5Cmathbf%20r%20%3D%20f%280%2C4%29%20-%20f%28-1%2C2%29%20%3D%2064%20-%2041%20%3D%20%5Cboxed%7B23%7D)
![\displaystyle \int_{(0,4)}^{(2,3)} \mathbf F \cdot d\mathbf r = f(2,3) - f(0,4) = 108 - 64 = \boxed{44}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint_%7B%280%2C4%29%7D%5E%7B%282%2C3%29%7D%20%5Cmathbf%20F%20%5Ccdot%20d%5Cmathbf%20r%20%3D%20f%282%2C3%29%20-%20f%280%2C4%29%20%3D%20108%20-%2064%20%3D%20%5Cboxed%7B44%7D)
Answer:
34
Step-by-step explanation:
2u=u+34
2u-u=34
u=34
-4(1)+10=6
-4(2)+10=2
-4(3)+10=-2
-4(4)+10=-6
-4(5)+10=-10
So d is the answer